Association between VEGF gene polymorphisms and breast cancer risk - Osman, Hala; Hassan, Mozan; Alfaki, Mohamed; Haj-Ali, Ghada (Biochemistry and biophysics reports, 2025)
Breast cancer (BC) poses a significant global health challenge. In Sudan, the absence of a national cancer registry has resulted in an underestimation of BC incidence. BC is notably the most common cancer among Sudanese women, especially affecting those under 50, with many cases diagnosed at advanced stages. Angiogenesis, driven by vascular endothelial growth factor (VEGF), plays a critical role in the progression and recurrence of BC. This study examines the relationship between the VEGF (rs699947) gene polymorphism and BC among Sudanese women in Khartoum State in 2022. Methodology: A case-control study was conducted with 30 BC patients, and tissue samples were collected for molecular analysis. DNA was extracted and genotyped for the VEGF (rs699947) polymorphism using allele-specific PCR. No statistically significant association was found between the VEGF-2578 C > A polymorphism and BC risk in our study population. Although the A allele was more prevalent in tumor tissues compared to normal tissues, with no significant correlation with tumor stage or grade. The study revealed that BC in Sudanese women often presents at younger ages and is predominantly invasive ductal carcinoma, with stage II being the most common. These findings emphasize the necessity for continued research to explore additional genetic factors and improve our understanding of BC and associated risks. Advancing early detection and prevention methods is vital, particularly for underrepresented populations. However, the small sample size in this study may limit the statistical power to detect significant associations, and thus, findings should be interpreted with caution. •Breast cancer is the leading malignancy among Sudanese women, often diagnosed at advanced clinical stages.•This case-control study investigated VEGF (rs699947) polymorphism in 30 breast cancer patients in Khartoum, Sudan.•The heterozygous TA genotype was most common; the A allele was more frequent in tumor tissue vs adjacent normal tissue.•Invasive ductal carcinoma was the predominant histological type, with stage II as the most frequently observed stage.•No significant link was found in this cohort, highlighting the need for broader genetic research in diverse populations.